Academic Integrity Policy Analysis of Publicly-Funded Universities in Ontario, Canada: A Focus on Contract Cheating - Miron, Jennie; McKenzie, Amanda; Eaton, Sarah Elaine; Stoesz, Brenda; Thacker, Emma; Devereaux, Lisa; Persaud, Nira; Steeves, Marcia; Rowbotham, Kate (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
In this article we report findings from a review of universities’ academic integrity policies in Ontario, Canada. The research team systematically extracted, reviewed, and evaluated information from policy documents in an effort to understand how these documents described contract cheating in Ontario universities (n = 21). In all, 23 policies were examined for contract cheating language. The elements of access, approach, responsibility, detail, and support were examined and critiqued. Additionally, document type, document title and concept(s), specific contract cheating language, presence of contract cheating definitions and policy principles were reviewed. Findings revealed that none of the universities’ policies met all of the core elements of exemplary policy, were reviewed and revised with less frequency than their college counterparts, lacked language specific to contract cheating, and were more frequently focused on punitive rather than educative approaches. These findings confirm that there is further opportunity for policy development related to the promotion of academic integrity and the prevention of contract cheating.